A model of trust in the work of an air traffic controller - Bonini, Deirdre (Trinity College (Dublin, Ireland). School of Psychology, 2005)
The research summarised in this thesis aimed at understanding the role of trust in the work of an air traffic controller (hereafter controller), as well as identifying the salient characteristics that a controller uses to decide whether to trust another or the technology they use in their work.
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin